Barkhausen Noise Signal Analysis of IS 2062 Steel and AISI D2 Tool Steel with Different Range of Magnetizing Frequency and Intensity - Diwakar V.; Sharma A.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
Abstract: Signal processing is essential to extract precise and transparent information about the characterization of the ferromagnetic materials produced during the magnetic Barkhausen noise (MBN) analysis. In the present research work, MBN signal obtained from two steels, i.e., IS-2062 steel and AISI D2 tool steel, is analyzed using MATLAB, where the shape and characteristics of the MBN signal distinguish materials properties of these two steels. The variation in Barkhausen noise signal profile is assessed, and a correlation between the material’s properties and the signal’s characteristics is obtained at various magnetizing frequency (MF). The raw MBN and average RMS profile change insignificantly within the IS 2062 steel. But, compared to the AISI D2 tool steel, there is a sudden drop in the peak and RMS profile within a wide range of the MF at constant magnetizing field intensity (MFI). BN signal’s characteristics correlated well with grain size and hardness for both steel and clearly, indicated that AISI D2 tool steel has a smaller grain size. Interestingly at low magnetic field intensity 200 Oe, no magnetic response was observed in AISI D2 steel, indicating the high hardness and more grain boundaries of this steel which hindered the magnetic domain wall activities at low magnetic field. But at higher magnetic field (500 Oe), magnetic response was obtained from AISI D2 tool steel, indicating the requirement of minimum magnetic field for domain wall motion. It is also demonstrated that the variation in MFI from 200 to 500 Oe and MF influences the shape of the hysteresis loop and its characteristics such as permeability, coercivity, and remanence. © 2022, Pleiades Publishing, Ltd.